Direct oxidation of H-2 to H2O2 over Pd-based catalysts: influence of oxidation state, support and metal additives - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
The influence of oxidation state (reduced and oxidized), support (ZrO2, Ga2O3, CeO2, SiO2, H-beta, ThO2, CeO2-ZrO2, BPO4 and Pd/Al2O3) and precious metal additives (Au, Pt, Rh and Ru) on the direct H2O2 synthesis has been investigated over Pd-based catalysts. For all the supports investigated herein, the oxidized Pd catalysts showed significantly superior H2O2 yields as compared to their reduced counterparts. The effect of the Pd oxidation state was found to be more important for determining the H2O2 yields than the particle size and surface area properties of the catalyst system. An excellent correlation was observed between the H2O2 selectivity and H2O2 decomposition activity of the oxidized Pd catalysts. The oxidized Pd catalysts showed almost an order of magnitude lower H2O2 decomposition activity than the reduced catalysts. The H2O2 yield in the H-2 to H2O2 oxidation passed through a maximum with increase in the An concentration. Although a similar effect was also observed in case of Pt, Au was found to be a superior promoter for the direct H2O2 synthesis process. Addition of Rh and Ru was found to be detrimental for the H2O2 yields; these results can be explained in terms of increased H2O2 decomposition activity and/or enhanced H-2 to H2O reaction activity in their presence. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: decomposition; direct synthesis; H2O2; metal additives; oxidation state; Pd catalysts; supports

Factors influencing decomposition of H2O2 over supported Pd catalyst in aqueous medium - Choudhary, Vasant R.; Samanta, C.; Choudhary, Tushar V. (Journal of Molecular Catalysis A-Chemical, 2006)
Since H2O2 decomposition can result in selectivity/yield loss in the direct H2O2 synthesis process from H-2 and O-2 over supported Pd catalysts, it is important to have an enhanced understanding about the factors affecting the H2O2 decomposition reaction. Herein, detailed studies have been undertaken to investigate the influence of different factors, such as (a) nature and concentration of acid in reaction medium, (b) nature and concentration of halide in presence and absence of acid in reaction medium, (c) pretreatment procedures and (d) catalyst modification by incorporation of different halides, on the H2O2 decomposition reaction over a 5% Pd/C catalyst in aqueous medium at 25 degrees C. This study has shown that the H2O2 decomposition activity is profoundly influenced by all the above factors. The effectiveness of the acids in suppressing the H2O2 decomposition activity decreased in the following order: hydroiodic acid > hydrobromic acid > hydrochloric acid >> acetic acid > phosphoric acid > sulfuric acid > perchloric acid. The ability of the acid to decrease the H2O2 decomposition activity was found to very strongly depend on the nature of its associated anion. Halides, such as iodide, bromide and chloride were particularly effective in suppressing the H2O2 decomposition activity. Oxidation pretreatment of the catalyst was found to strongly suppress its H2O2 decomposition activity, while a reduction treatment was found to promote its activity. A gradual decrease in the H2O2 decomposition activity of the catalyst was observed with each successive usage due to in situ sub-surface oxidation of Pd by H2O2. Halide incorporation either via the reaction medium or prior catalyst modification had a similar qualitative effect on the H2O2 decomposition activity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: acid; H2O2 decomposition; H2O2 synthesis; halides; Pd catalysts; pretreatment

Direct synthesis of hydrogen peroxide from hydrogen and oxygen: an overview of recent developments in the process - Samanta, Chanchal (Applied Catalysis A-General, 2008)
Hydrogen peroxide (H(2)O(2)) is an important commodity chemical and its demand is growing significantly in the chemical synthesis due to its ``green'' character. Currently, H(2)O(2) is produced almost exclusively by the anthraquinone auto-oxidation (AO) process. The AO process involves indirect oxidation of hydrogen and thus avoids potentially explosive H(2)/O(2) mixture. However, this large-scale process presents significant safety issues associated with the transport of bulk H(2)O(2). Moreover, the AO process can hardly be considered ail environmentally friendly method. In view of this, more economical and environmentally cleaner routes have been explored for the production of H(2)O(2). The liquid-phase catalytic direct synthesis of H(2)O(2) from H(2) and O(2) offers an attractive green technology for small-scale/onsite production of H(2)O(2). However, the direct synthesis process suffers from two major drawbacks: (i) potential hazards associated with H(2)/O(2) mixtures and (ii) poor selectivity for H(2)O(2) because the catalysts used for H(2)O(2) synthesis are also active for its decomposition and hydrogenation to water as well as for H(2) combustion. These serious issues and the recent developments in the direct H(2)O(2) synthesis are discussed in this review. The roles of protons (H(+)) and halide ions in promoting the H(2)O(2) selectivity are also examined in detail. (C) 2008 Elsevier B.V. All rights reserved
Keywords: Bimetallic catalysts; Direct H(2)O(2) synthesis; Microreactor technology; Pd catalysts